2017
DOI: 10.1038/s41598-017-14411-y
|View full text |Cite|
|
Sign up to set email alerts
|

GRAFENE: Graphlet-based alignment-free network approach integrates 3D structural and sequence (residue order) data to improve protein structural comparison

Abstract: Initial protein structural comparisons were sequence-based. Since amino acids that are distant in the sequence can be close in the 3-dimensional (3D) structure, 3D contact approaches can complement sequence approaches. Traditional 3D contact approaches study 3D structures directly and are alignment-based. Instead, 3D structures can be modeled as protein structure networks (PSNs). Then, network approaches can compare proteins by comparing their PSNs. These can be alignment-based or alignment-free. We focus on t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
66
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 31 publications
(68 citation statements)
references
References 65 publications
(126 reference statements)
2
66
0
Order By: Relevance
“…that measure different network properties. One such baseline PSN feature is Existing-all, which integrates seven network properties to represent a PSN [6]. Another popular PSN feature that counts different types of network patterns is the concept of graphlets; graphlets are subgraphs or small lego-like building blocks of complex networks [26].…”
Section: Motivation and Related Workmentioning
confidence: 99%
See 2 more Smart Citations
“…that measure different network properties. One such baseline PSN feature is Existing-all, which integrates seven network properties to represent a PSN [6]. Another popular PSN feature that counts different types of network patterns is the concept of graphlets; graphlets are subgraphs or small lego-like building blocks of complex networks [26].…”
Section: Motivation and Related Workmentioning
confidence: 99%
“…PSNs. Also, this approach only used the concept of regular graphlets, while we also test a newer concept of ordered graphlets [30] (see Methods), which outperformed regular graphlets in the GRAFENE study [6].…”
Section: Motivation and Related Workmentioning
confidence: 99%
See 1 more Smart Citation
“…Nodes 4, 5 , 6 and 7 are connected by a 3-dimensional simplex (tetrahedron, in blue). Pržulj, 2007;Yaveroglu et al, 2014), as well as between protein 3D structures represented by networks (Malod-Dognin and Pržulj, 2014;Faisal et al, 2017). In particular, graphlets have been used to characterize and compare the local wiring patterns around nodes in a PPI network (Milenković and Pržulj, 2008), which revealed that molecules involved in similar functions tend to be similarly wired (Davis et al, 2015).…”
Section: Motivationmentioning
confidence: 99%
“…These features can be broadly categorized into (i) sequence features, i.e., codon frequency, GC content, gene length [16][17][18], (ii) topological features, i.e., degree centrality, cluster coefficient [19][20][21][22], and (iii) functional features, i.e., homology, gene expression cellular localization, functional domain and other molecular properties [10,[23][24][25][26]. More recent studies about the 3D structure of proteins can also be incorporated in topological features set [27,28].…”
mentioning
confidence: 99%